(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
This cross sectional study was carried out in the department of radiology & imaging, Neurosurgery, Spine Surgery Unit of BSMMU and Sir Salimullah Medical College & Mitford Hospital, DMCH, during 1st January 2006 to 31st December 2007, to establish the diagnostic usefulness of MRI in evaluation of spinal tumours .A total of 57 patients having nerve sheath and meningioma tumour were enrolled in this study. The age ranged from 10 to 67 years and the maximum number was found in the age group of 31-40 years. The mean age was 39.9 years with standard deviation (SD) ±15.2 years. Out of 57 patients, 57.9% were male and rest 42.1% were female patients and male female ratio was 1.4:1. In MRI diagnosis there were highest incidence of nerve sheath tumours 43 cases in intradural extramedullary compartment and 14.3% was meningioma the next commonest tumour in this compartment. Schwannoma was the most commone lesion in intradural extramedullary tumours, which was 40.4%, followed by Neurofibroma 35.1% and meningioma 24.6% by histopathology among all intradural extramedullary spinal tumours. Commonest location of intradural extramedullary spinal tumours were found in thoracic (36 cases) followed by cervical (14 cases) and lumbar (7 cases). J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 42-45